2018
DOI: 10.1111/nyas.13706
|View full text |Cite
|
Sign up to set email alerts
|

The effects of music‐supported therapy on motor, cognitive, and psychosocial functions in chronic stroke

Abstract: Neuroplasticity accompanying learning is a key mediator of stroke rehabilitation. Training in playing music in healthy populations and patients with movement disorders requires resources within motor, sensory, cognitive, and affective systems, and coordination among these systems. We investigated effects of music-supported therapy (MST) in chronic stroke on motor, cognitive, and psychosocial functions compared to conventional physical training (GRASP). Twenty-eight adults with unilateral arm and hand impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 51 publications
0
40
0
6
Order By: Relevance
“…Active music playing as a therapy is an enjoyable activity that involves complex and coordinated movements while placing a high demand on cognitive functions, such as attention, working memory, and executive function [27,86]. It has been demonstrated that active music engagement through instrument playing promotes significant cognitive benefits to attention and verbal memory [87,88]. Moreover, several neurologic music therapy interventions have been developed specifically for cognitive rehabilitation focusing on auditory attention and perception training, memory training, and executive function training [89][90][91].…”
Section: Future Researchmentioning
confidence: 99%
“…Active music playing as a therapy is an enjoyable activity that involves complex and coordinated movements while placing a high demand on cognitive functions, such as attention, working memory, and executive function [27,86]. It has been demonstrated that active music engagement through instrument playing promotes significant cognitive benefits to attention and verbal memory [87,88]. Moreover, several neurologic music therapy interventions have been developed specifically for cognitive rehabilitation focusing on auditory attention and perception training, memory training, and executive function training [89][90][91].…”
Section: Future Researchmentioning
confidence: 99%
“…In another RCT, 28 chronic stroke patients without extensive musical experience received either 30-h of music-supported therapy (MST) or conventional physical training over a 10-week period (Fujioka et al, 2018). The MST protocol included mapping functional movements on playing musical instruments, which was based on the NMT technique (Thaut, 2005), as well as music-making with a therapist.…”
Section: Music-based Interventions For Ef and Ap Neurorehabilitation mentioning
confidence: 99%
“…Training in playing music in healthy populations and patients with movement disorders requires resources within motor, sensory, cognitive, and affective systems, and coordination among these systems. The music-supported therapy in chronic stroke on motor, cognitive, and psychosocial functions compared to conventional physical training (Fujioka et al, 2018). The music-based movement program improves physical function and sleep quality in people with multiple sclerosis (Young et al, 2017).…”
Section: Discussionmentioning
confidence: 99%